Educational contents and innovative competencies for training and research in technology industry - Mario Losasso (Agathón)
The birth of Architectural Technology dates back to the end of the 1960s and it is an innovation in the spectrum of courses offered in the Architecture department. The evolution of this subject has given rise to different areas that have originally contributed to increasing awareness of the architecture project as part of the building process. Today, the new educational challenges are facing emerging scenarios of the building industry digitalization, which contribute to determining structures of greater efficiency, linked to enabling technologies to manage intangible components and information.